Efficient degradation of chlorobenzene in a non-thermal plasma-liquid system enabled by Fe3O4@C catalysts - Caihong Qin; Xiaoge Zhang; Xuan Qu; Zichen Xue; Qiaoqiao Jiao; Xueyang Fan; Junji Lu (Journal of Environmental Chemical Engineering, 2026)

Low-temperature plasma catalysis for VOCs control: Mechanistic insights and hybrid strategies - Junhui Li; Yuan Liu; Zhencheng Xing; Yide Jiang; Zichen Xu; Xuebin Lu; Yifei Sun; Yong Yin (Environmental Research, 2026)

Preparation and properties of an in-situ sealing and water retention double-network gel for inhibiting coal spontaneous combustion - Jiangle Wu; Caiping Wang; Jun Deng; Yang Xiao; Yi Lu; Zichen Shi; Zujin Bai; Jiuxiao Lu (Journal of Environmental Chemical Engineering, 2026)

Reconstruction of temperature and soot volume fraction in C2H4/NH3 diffusion flame based on the improved two-color method integrated with the absorption coefficient ratio model - Zijun Tian; Shu Zheng; Yu Yang; Weiguang Cai; Zichen Lv; Yao Kong; Hao Liu; Qiang Lu (Fuel, 2026)

Discrete element modeling and experimental validation of the multi-scale based coronal tea plant root-soil complex - Kuan Qin; Junjie Lu; Jin Zhang; Chengmao Cao; Zichen Huang; Xuechen Zhang; Weidong Gao; Xu Zhu; Kang Xue; Liwei Wang; Zhengmin Wu; Haijun Bi; et al. (Computers and Electronics in Agriculture, 2026)

A hybrid POD-LSTM framework for efficient vortex-induced vibration prediction in marine risers via multi-fidelity data fusion - Kang Lu; Zheng Zeng; Sheng Zhou; Xiong Xiong; Rongchun Hu; Zichen Deng (Ocean Engineering, 2026)

The synergy of light irradiation, TiO2, and Fe3O4 boosts biohydrogen production from the dark fermentation at room temperature - Shuai Tang; Jia Ai; Zichen Liu; Weizhong Jiang; Buchun Si; Haifeng Lu (Bioresource Technology, 2025)

Modeling hydro-thermal processes in fractured geothermal reservoirs using embedded discrete fracture model (EDFM) and MRST - Tongchao Nan; Tianwei Hu; Zichen Wang; Jiangjiang Zhang; Jina Yin; Yifan Xie; Jichun Wu; Chunhui Lu (Advances in Water Resources, 2025)

Hetero-structured hydrogel with transition layer: Achieving synergistic sensing-actuating integration for intelligent ship - Bingchen Zhou; Tianzong Jiang; Yanqi Yin; Zewei Sun; Zichen Lu; Shili Gai; He Ding; Piaoping Yang (Chemical Engineering Journal, 2025)

Biohydrogen production from food waste using a novel rotational drum reactor integrated with milli-magnetite - Zichen Liu; Shuai Tang; Yi Ren; Pengyu Chen; Dingna Ma; Buchun Si; Weizhong Jiang; Haifeng Lu; Yuanhui Zhang (Bioresource Technology, 2025)

Fractal Characterization of Pore Structure and Mechanical Degradation in Carbonate Rocks Under Acid Dissolution - Xin Liu; Chen Wang; Ting Lu; Xiaosong Wen; Zichen Li; Yujun Zuo (Geotechnical and Geological Engineering, 2025)

Quality changes in the physiology, behaviour, nutrition, and taste of Urechis unicinctus during waterless live transportation - Teng Teng; Yuchun Lu; Zichen Deng; Shuqi Wang; Yuting Yang; Huihong Li; Chun-E Liu (Food Chemistry, 2025)

Significant insights of CaO2 promoting heavy metal complexes removal during a plasma process - Meiqian Lu; Rong Li; Zichen Wang; Yue Liu; Guodong Zhang; Qiuling Ma; Jian Zhou; He Guo; Tiecheng Wang (Journal of Environmental Management, 2025)

An efficient and global method for orbit uncertainty propagation near irregular-shaped asteroids - Xuefen Zhang; Haibin Shang; Jucheng Lu; Zichen Zhao (Advances in Space Research, 2025)

Adsorption performance and mechanism of HFO/pumice composites for phosphate in water - Jian Huang; Xianjin Qiu; Hua Zhang; Chenxi Zhang; Zhuoyi Lu; Tao Luo; Chunhua He; Jiamei Zhang; Zichen Shuai (Limnologica, 2025)

A review of fluorescence imaging system supported by excitation-emission matrix for fruit and vegetable quality estimation - Zichen Huang; Yoshito Saito; Tianqi Gao; Dimas Firmanda Al Riza; Renfu Lu; Haiyan Cen; Naoshi Kondo; Ken Abamba Omwange (Food Control, 2025)

The removal of antibiotic resistance bacteria and genes and inhibition of RP4 plasmid-mediated conjugative transfer by citric acid chelated Fe(II) catalyzing peroxymonosulfate systems: Performance and mechanisms - Hengrui Liu; Lu An; Zixuan Gao; Zichen Duan; Bin Luo; Yifan Sun; James M Tiedje; Jie Gu; Xiaojuan Wang (Chemical Engineering Journal, 2024)

Numerical simulation of soot and NO formation in DME/gasoline laminar co-flow diffusion flames - Shu Zheng; Zichen Lv; Yu Yang; Hao Liu; Qiang Lu (Fuel, 2024)

Novel Coumarins Derivatives for A. baumannii Lung Infection Developed by High-Throughput Screening and Reinforcement Learning - Jing Li; Zhou Lu; Liuchang Wang; Huiqing Shi; Bixin Chu; Yingwei Qu; Zichen Ye; Di Qu (Journal of Neuroimmune Pharmacology, 2024)
With the increasing resistance of Acinetobacter baumannii ( A. baumannii ) to antibiotics, researchers have turned their attention to the development of new antimicrobial agents. Among them, coumarin-based heterocycles have attracted much attention due to their unique biological activities, especially in the field of antibacterial infection. In this study, a series of coumarin derivatives were synthesized and screened for their bactericidal activities (Ren et al. 2018; Salehian et al. 2021). The inhibitory activities of these compounds on bacterial strains were evaluated, and the related mechanism of the new compounds was explored. Firstly, the MIC values and bacterial growth curves were measured after compound treatment to evaluate the antibacterial activity in vitro. Then, the in vivo antibacterial activities of the new compounds were assessed on A. baumannii -infected mice by determining the mice survival rates, counting bacterial CFU numbers, measuring inflammatory cytokine levels, and histopathology analysis. In addition, the ROS levels in the bacterial cells were measured with DCFH-DA detection kit. Furthermore, the potential target and detailed mechanism of the new compounds during infection disease therapy were predicted and evidenced with molecular docking. After that, ADMET characteristic prediction was completed, and novel, synthesizable, drug-effective molecules were optimized with reinforcement learning study based on the probed compound as a training template. The interaction between the selected structures and target proteins was further evidenced with molecular docking. This series of innovative studies provides important theoretical and experimental data for the development of new anti- A. baumannii infection drugs.

Optimal coordination contracts for manufacturer and streamer joint emission reduction and low-carbon publicity in a live-streaming supply chain - Liangjun Peng; Gang Lu; Mingwu Liu; Zichen Zou (Environment, Development and Sustainability, 2024)

Simulation and experiment of air-duct heating equipment using electricity in a sheep barn using computational fluid dynamics - Zichen Liu; Honglei Cen; Min Lu; Jingbin Li; Qiang Cai; Jing Nie; Baoqin Wen; Yalei Xu (Computers and Electronics in Agriculture, 2024)

O2 plasma-modified carbon nanotube for sulfamethoxazole degradation via peroxymonosulfate activation: Synergism of radical and non-radical pathways boosting water decontamination and detoxification - Shiqi Liu; Zichen Zhang; Rui Lu; Yuankun Mao; Huiru Ge; Can Liu; Chenxi Tian; Siyuan Yin; Li Feng; Yongze Liu; Chao Chen; Liqiu Zhang (Chemosphere, 2023)

Enhancing infrared electrochromic properties of the poly(styrene sulfonate) doped polyaniline composite film by morphology regulation - Leipeng Zhang; Tingting Hao; Shanshan Song; Bo Wang; Dongqi Liu; Zichen Ren; Wenchao Liu; Yike Zhang; Gaoping Xu; Xiangqiao Yan; Yuan Lu; Yao Li (Chemical Engineering Journal, 2023)

Heart valve-inspired self-lubricating anticoagulant surfaces - Yang Cheng; Zhiwei Yang; Xiaodan Gou; Qing Yang; Zichen Zhang; Shiyu Cui; Yuhua Ren; Lihong Fan; Haifeng Zhang; Zheng Fang; Yu Lu; Lin Kai; et al. (Chemical Engineering Journal, 2023)

Giant nonlocal edge conduction in the axion insulator state of MnBi2Te4 - Yaoxin Li; Chang Liu; Yongchao Wang; Zichen Lian; Shuai Li; Hao Li; Yang Wu; Hai-Zhou Lu; Jinsong Zhang; Yayu Wang (Science Bulletin, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Enhanced cyanogen chloride formation after UV/PS and UV/H2O2 pre-oxidation and chlorination in natural river water - Jie Xu; Yang Guo; Qian Yang; Xueling Bai; Runhua Lu; Menghui Liu; Zichen Kuang; Luo Zhang; Jing Li (Journal of Environmental Sciences, 2023)

Deep Learning Convolutional Neural Network Applying for the Arctic Acoustic Tomography Current Inversion Accuracy Improvement - Kangkang Jin; Jian Xu; Zichen Wang; Can Lu; Long Fan; Zhongzheng Li; Jiaxin Zhou (Journal of Marine Science and Engineering, 2021)
Warm current has a strong impact on the melting of sea ice, so clarifying the current features plays a very important role in the Arctic sea ice coverage forecasting study field. Currently, Arctic acoustic tomography is the only feasible method for the large-range current measurement under the Arctic sea ice. Furthermore, affected by the high latitudes Coriolis force, small-scale variability greatly affects the accuracy of Arctic acoustic tomography. However, small-scale variability could not be measured by empirical parameters and resolved by Regularized Least Squares (RLS) in the inverse problem of Arctic acoustic tomography. In this paper, the convolutional neural network (CNN) is proposed to enhance the prediction accuracy in the Arctic, and especially, Gaussian noise is added to reflect the disturbance of the Arctic environment. First, we use the finite element method to build the background ocean model. Then, the deep learning CNN method constructs the non-linear mapping relationship between the acoustic data and the corresponding flow velocity. Finally, the simulation result shows that the deep learning convolutional neural network method being applied to Arctic acoustic tomography could achieve 45.87% accurate improvement than the common RLS method in the current inversion.

A new prediction method of seafloor hydrothermal active field based on wavelet neural network - Longlong Liu; Zichen Lu; Di Ma; Mingjiao Ma (Marine Geophysical Research, 2020)

MOTS-c peptide regulates adipose homeostasis to prevent ovariectomy-induced metabolic dysfunction - Huanyu Lu; Ming Wei; Yue Zhai; Qingyang Li; Zichen Ye; Li Wang; Wenjing Luo; Jingyuan Chen; Zifan Lu (Journal of Molecular Medicine, 2019)